VLF/LF Reflectivity of the Polar Ionosphere, 4 May - 5 July 1975 - Rasmussen,John E; McLain,Ralph J; Turtle,John P; Klemetti,Wayne I (1976)
This report provides a summary of high latitude ionospheric reflectivity as observed by the USAF high resolution VLF/LF ionosounder operating in northern Greenland. Ionospheric reflectivity parameters, including reflection heights and coefficients, are presented as a function of time of day. VLF long path propagation measurements, along with magnetometer and riometer data, are presented as supplemental information. (Author)